2018
DOI: 10.3892/ol.2018.8166
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells expressing interleukin-18 inhibit breast cancer in a mouse model

Abstract: Development of an improved breast cancer therapy has been an elusive goal of cancer gene therapy for a long period of time. Human mesenchymal stem cells derived from umbilical cord (hUMSCs) genetically modified with the interleukin (IL)-18 gene (hUMSCs/IL-18) were previously demonstrated to be able to suppress the proliferation, migration and invasion of breast cancer cells in vitro. In the present study, the effect of hUMSCs/IL-18 on breast cancer in a mouse model was investigated. A total of 128 mice were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 42 publications
(46 reference statements)
1
22
0
Order By: Relevance
“…Several preclinical studies have demonstrated anti‐tumor efficacy using genetically‐engineered MSCs to home transgenes to tumor stroma . In these studies, the modified gene either encoded for a secreted protein that had either a direct or indirect effects on tumor cells, or a ‘suicide’ gene that encoded for an enzyme that converted a prodrug into cytotoxic metabolites; an approach known as gene‐directed enzyme‐producing therapy (GDEPT) …”
Section: Introductionmentioning
confidence: 99%
“…Several preclinical studies have demonstrated anti‐tumor efficacy using genetically‐engineered MSCs to home transgenes to tumor stroma . In these studies, the modified gene either encoded for a secreted protein that had either a direct or indirect effects on tumor cells, or a ‘suicide’ gene that encoded for an enzyme that converted a prodrug into cytotoxic metabolites; an approach known as gene‐directed enzyme‐producing therapy (GDEPT) …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that human umbilical cord MSCs transduced with adenoviral vectors expressing IFNβ effectively inhibit the growth of breast cancer cells through induction of apoptosis (Shen et al, 2016). Interleukins are another group of cytokines used as tumor-suppressing agents (Chen et al, 2008;Liu et al, 2018). A recent study using lentiviral transductions showed that human umbilical cord MSCs expressing interleukin-18 inhibit the proliferation and metastasis of breast cancer in mice (Liu et al, 2018).…”
Section: Mscs As Carriers Of Anti-cancer Payloadsmentioning
confidence: 99%
“…Interleukins are another group of cytokines used as tumor-suppressing agents (Chen et al, 2008;Liu et al, 2018). A recent study using lentiviral transductions showed that human umbilical cord MSCs expressing interleukin-18 inhibit the proliferation and metastasis of breast cancer in mice (Liu et al, 2018). Genetically engineered MSCs with TRAIL have also shown strong anti-tumor activity in different types of cancer (Ciavarella et al, 2012;Fakiruddin et al, 2014;Guo et al, 2016;Jiang et al, 2016).…”
Section: Mscs As Carriers Of Anti-cancer Payloadsmentioning
confidence: 99%
“…Furthermore, IL-18 inhibited HCC growth by priming NK cells trafficked to the liver [200]. Mesenchymal stem cells-expressing IL-18 inhibited the proliferation and metastasis of breast cancer cells by activating immunocytes and immune cytokines, downregulating the proliferation marker Ki-67 and suppressing tumor angiogenesis [201]. Collectively, IL-18-based immunotherapy might be a promising therapeutic strategy for cancer.…”
Section: The Emerging Role Of Inflammasome-dependent Cytokines In mentioning
confidence: 99%